2006 Information and communications for development : global trends and policies. (World Bank e-Library., 2006)
"The report is essential reading for policy makers, government workers, and academics pursuing the goal of equitable, sustainable development across the world."--N.R. Narayana Murthy, Chairman and Chief MentorInfosys Technologies Ltd. Information and communication technology (ICT) is rapidly evolving, changing rich and poor societies alike. It has become a powerful tool for participating in the global economy and for offering new opportunities for development efforts. ICT can and should advance economic growth and reduce poverty in developing countries. It has been 20 years since th